2019
DOI: 10.1128/aem.00935-19
|View full text |Cite
|
Sign up to set email alerts
|

Erwinia amylovora Auxotrophic Mutant Exometabolomics and Virulence on Apples

Abstract: The Gram-negative bacterium Erwinia amylovora causes fire blight disease of apples and pears. While the virulence systems of E. amylovora have been studied extensively, relatively little is known about its parasitic behavior. The aim of this study was to identify primary metabolites that must be synthesized by this pathogen for full virulence. A series of auxotrophic E. amylovora mutants, representing 21 metabolic pathways, were isolated and characterized for metabolic defects and virulence in apple immature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 73 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…2015; Klee et al . 2019a). The ability of the Ea⊿ghxP::Cam r mutant to cause disease was monitored in immature pear and apple fruit assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2015; Klee et al . 2019a). The ability of the Ea⊿ghxP::Cam r mutant to cause disease was monitored in immature pear and apple fruit assays.…”
Section: Resultsmentioning
confidence: 99%
“…2014, 2015; Klee et al . 2019a). Some auxotrophs display reduced growth and virulence, while others have minimal effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five days later, the larvae (7-days-old, approximately 25 mg fresh aphid material per sample) were snap-frozen in liquid nitrogen and stored at –80°C. Following extraction of metabolites (protocol in Text S1D ), metabolites were separated using a Waters XSelect HSS T3 column (100 Å, 5 ÎŒm, 2.1 mm × 100 mm) fitted with a Restex UltraShield 0.2-ÎŒm precolumn filter and analyzed on a Thermo Exactive Plus Orbitrap ( 72 – 74 ). Blanks and a pooled QC sample were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that amino acid metabolism might be important for virulence [43][44][45]. In E. amylovora, mutants deficient in arginine, isoleucine/valine, and tryptophan metabolism exhibited reduced virulence [44], and the argD mutant of E. amylovora not only led to arginine auxotrophy, but also exhibited attenuated or no virulence in apples and pears [45]. A methionine metabolism regulator MetR has been identified as a new virulence regulator [46].…”
Section: Differential Regulation Of Amino Acid and Peptide Biosynthesmentioning
confidence: 99%